Focal adhesion kinase and its epigenetic interactors as diagnostic and therapeutic hints for pediatric hepatoblastoma - Braghini, Maria Rita; De Stefanis, Cristiano; Tiano, Francesca; Castellano, Aurora; Cicolani, Nicolo’; Pezzullo, Marco; Tocco, Valeria; Spada, Marco; Alaggio, Rita; Alisi, Anna; Francalanci, Paola (Frontiers in Oncology, 2024)
Background: Hepatoblastoma (HB) is the most common pediatric hepatic malignancy. Despite the progress in HB treatment, investigating HB pathomechanisms to optimize stratification and therapies remains a focal point to improve the outcome for high-risk patients.Methods: Here, we pointed to explore the impact of these mechanisms in HB. An observational study was performed on liver samples from a cohort of 17 patients with a diagnosis of HB and two normal liver samples. The in vitro experiments were executed on the Huh6 human HB cell line treated with the FAK inhibitor TAE226.Our results highlight a significant up-regulation of mRNA and protein expression of FAK in livers from HB with respect to normal livers. The increased protein expression of total and Tyr397 phosphorylated FAK (pTyr397FAK) was significantly correlated with the expression of some epigenetic regulators of histone H3 methylation and acetylation. Of note, the expression of pTyr397FAK, N-methyltransferase enzyme (EZH2) and tri-methylation of the H3K27 residue correlated with tumor size and alpha-fetoprotein (AFP) levels. Finally, TAE226 caused a significant reduction of pTyr397FAK, epigenetic regulators, AFP, EPCAM, OCT4, and SOX2, in association with anti-proliferative and pro-apoptotic effects on HB cells.Our results suggest a role of FAK in HB that requires further investigations mainly focused on the exploration of its effective diagnostic and therapeutic translatability.